Urban development and housing in india 1947 to 2007 - Dwivedi, Rishi Muni (ed.) (New Delhi, 2007)
The broad objective of urbanization policy should be to secure balanced development between large, medium-sized, and small industries, and between rural and urban areas. Housing is an activity that is typically labor intensive and, therefore, fits in well with the pattern of development envisaged for India. The provision of shelter is a basic need which must be met. Housing construction also creates much-needed employment for the unskilled and, therefore, income for the relatively poor. This study provides a detailed introduction to urban development and housing policies in India. Additionally, it presents edited extracts on the subject from India's Five Year Plans and contains select schemes of urban development and housing which are presently in operation.
Keywords: Urban development